2021
DOI: 10.1371/journal.pone.0247073
|View full text |Cite
|
Sign up to set email alerts
|

Oral health practices and oral hygiene status as indicators of suicidal ideation among adolescents in Southwest Nigeria

Abstract: Background Oral health is a less-recognized correlate of overall and mental wellbeing. This study aimed to assess the relationship between suicidal behavior (ideation and attempt) and oral health practices and status, and to determine the effect of sex on these associations among Nigerian adolescents. Methods Household survey data were collected from 10 to 19-year-old adolescents in southwestern Nigeria. Dependent variables were daily tooth brushing, daily consumption of refined carbohydrates between meals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
1
Order By: Relevance
“…(Table 1). To determine the level of suicide probability, SPS total mean scores obtained from studies in similar age groups were found to be lower than the mean scale score in our study (Arun et al, 2021;Asante et al, 2017;Folayan et al, 2021). In this study, contrary to the literature, the high SPS total mean scores reveal the importance of early detection of suicide by evaluating the risk of suicide among university students and taking precautions as soon as possible.…”
Section: Discussioncontrasting
confidence: 70%
“…(Table 1). To determine the level of suicide probability, SPS total mean scores obtained from studies in similar age groups were found to be lower than the mean scale score in our study (Arun et al, 2021;Asante et al, 2017;Folayan et al, 2021). In this study, contrary to the literature, the high SPS total mean scores reveal the importance of early detection of suicide by evaluating the risk of suicide among university students and taking precautions as soon as possible.…”
Section: Discussioncontrasting
confidence: 70%
“…An interesting point is the oral health problems. A considerable number of studies have provided evidence that oral health is related to suicidal thoughts [ 35 37 ], but its importance has been underestimated compared to other variables, such as depression. This may be because oral health problems abandon the life-giving pleasure of enjoying good foods.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Second, COVID-19–associated psychological distress may change oral health–related behaviors. 11 , 29 Psychological distress caused by depression, 30 loneliness, and suicidal ideation 31 is known to be associated with a lower frequency of toothbrushing. Because social isolation increased during the pandemic lockdown, emotional distress increased, which may have negatively affected toothbrushing frequency.…”
Section: Discussionmentioning
confidence: 99%